PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK PENDAPAT SISWA TENTANG PELAKSANAAN LAYANAN KONSELING KELOMPOK - Suryani suryani; Khairani Khairani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2017)
Service counseling the group constitute service that helps alleviating the problems who experienced by the learners so that is reached developments who optimal. Reality on the ground that the proces implementation counseling services the group have not been effective in helping alleviating the problems student.The aim of this research describe students' opinions about the implementation of counseling services group be seen from time the implementation, stage the implementation, the role of group leader, the role members of the group and the achievement objectives counseling services the group. Types of descriptive research, with the findings the research, opinions students about the implementation of counseling service group in SMAN 6 Padang runs with well.